임실 숙성동굴에서 분리된 균주를 이용한 체다치즈 현장적용 - 강아현; Aa-hyeon Kang; 최희영; Hee-young Choi; 서일환; Il-hwan Seo; 박은하; Eun-ha Park; 강석봉; Seok-bong Kang; 정석근; Seok-geun Jeong (Journal of Dairy Science and Biotechnology, 2025)
This study examined three strains of lactic acid bacteria (LAB) collected from the first cheese ripening room in Imsil, Jeollabuk-do, South Korea. The identified strains included Lactococcus lactis subsp. lactis, L. lactis subsp. cremoris, and Streptococcus thermophiles, which are commonly used as cheese starters. Cheddar cheese containing the three strains was prepared to determine the change in quality during ripening. During ripening, no significant differences in pH, LAB, and chemical composition were observed but non-protein nitrogen and non-casein nitrogen levels were higher than the control. Free amino acids analysis revealed higher leucine and valine levels. Electronic-nose indicated that 2-propanol, 1-propanol, and hexane levels were higher in the control. The AHS, NMS, ANS, and PKS were found to be higher in the control using electronic-tongue. The three starters were not discernable in the sensory test. The selected strains can therefore be applied in the field after research into augmenting LAB vitality and can be used as cheese starters that are unique to Imsil.